Regulation of the Dynamics of Creating High-Tech Products - Batkovskiy, Aleksandr; Leonov, Aleksandr; Pronin, Aleksey; Chursin, Alexander; Nesterov, Evgeniy (International Journal of Engineering and Technology, 2018)
The existing models for regulating the dynamics of the creation of science-intensive products are very fragmented; they are based on various initial data and do not allow giving a comprehensive assessment of the feasibility of RandD for the creation of science-intensive products within a given time, especially in risk.Financial and economic risk; scientific, industrial and technological risk. Taking into account these types of risk, we introduce a methodical tool. This is a complex model for regulating economic dynamics designed for a probabilistic and cost description of the dynamics and results of the creation of science-intensive products.The model provides a complex tech-economic evaluation of projects to develop high-tech products in risk. This model has a universal character and can be used in all branches of economics of a technologically developed country. In practice, this complex model can be useful at the stage of selection of competing organizations designs with the purpose of evaluating their capacity to implement projects, as well as at the stage of adjusting the funding plan and cost estimates for the creation of science-intensive products.This model may be used in planning bodies to assess the capabilities of design organizations in the implementation of orders for the creation of science-intensive products.Â Â